Experimental investigations for development of Nylon6-Al-Al2O3 alternative FDM filament. Issue 2 (21st March 2016) - Singh Boparai, Kamaljit; Singh, Rupinder; Singh, Harwinder
Abstract : Purpose: The purpose of this paper is to fabricate Nylon6-Al-Al2O3 -based alternative fused deposition modeling process (FDM) feedstock filament in place of commercial acrylonitrile butadiene styrene (ABS) filament (having required rheological and mechanical properties) for rapid manufacturing (RM) and rapid tooling (RT) applications. The detailed steps for fabrication of alternative FDM feedstock filament (as per field application) with relatively low manufacturing cost and tailor-made properties have been highlighted. Design/methodology/approach: The rheological and mechanical suitability of nylon6-Al-Al2O3 feedstock filament has been investigated experimentally. The approach is to predict and incorporate essential properties such as flow rate, flexibility, stiffness and mechanical strength at processing conditions and compared with commercial ABS material. The proportions of various constituents have been varied to modify and improve rheological behavior and mechanical properties of alternative FDM feedstock filament. Findings: The alternative material of feed stock filament was successfully developed and loaded in commercial FDM setup without changing any hardware and software. The result of study suggests that the newly developed composite material filament has relatively poor mechanical properties but have highly thermal stability and wear resistant as compared to ABS filament and hence can be used for tailor-made applications. Research limitations/implications: In this work, no additive was added for improving the bond formation of metal and polymeric materials. The newly developed filament was prepared on single screw extruder. For more uniform mixing of metal and polymeric materials, further studies may be conducted on twin screw extruder. Also, for the present research work, the testing of newly developed filament has been limited up to mechanical testing, which may be extended to chemical and thermal analysis to understand thermal stability and degradation mechanism of newly developed composite material. Practical implications: The proportion of filler material (Al-Al2O3) in Nylon6 matrix was set as a constraint, which was adjusted based upon melt flow index of original equipment manufacturer developed material (ABS), and temperature conditions were available at FDM nozzle (so that hardware and software system of commercial FDM setup need not to be altered). Originality/value: The present approach outlined selection, processing, fabrication and testing procedure for alternate feedstock filament, which fulfills the necessary requirements of FDM process and has been customized for RT and RM applications. This work highlights mechanical strength evaluation of feedstock filament (which is necessary before the loading of material in FDM system). The potential applications of this investigation include RM of functional parts, tailor-made grinding tools for dentists and RT of metal matrix composite having complex geometry.